MENINGKATKAN KEMAMPUAN MEMBACA KATA PADA ANAK TUNAGRAHITA RINGAN MELALUI METODE P2R - Ayu Mustika Sari (Universitas Negeri Padang, 2014)
This research is motivated by problem that researches in the field found that mild mental retardation in a child class V/C who cannot read. Therefore the researcher seeks to help children improve reading skills through methods P2R said.this research aim to improve the ability to read words on a child class mild mental retardation V/C in SLB Muhammadiyah Pauh IX Padang. This type of research is a single subject research (SSR). The design of this study A-B-A. where A is the baseline condition of the initial condition in the children’s ability to read the word before the given action. Condition B is a condition in wich a child is given treatment intervention through P2R method. While the condition A2 is the initial condition after the intervention is no longer given. The result of this study shows that the ability to read words X class V/C in SLB Muhammadiyah Pauh IX Padang increased after intervention by the method given P2R. the baseline condition children scored 40%, the intervention condition children obtained the highest score is 100%, whereas in the baseline condition (A2) of the children scored 100%. Thus proved that method can improve the reading skills P2R word mental retardation in children SLB Muhammadiyah Pauh IX Padang. Based on the result of the study, the researchers gave suggestions to teachers for using the P2R as a method to improve reading skills for children tunagrahita.